The production of difference and maintenance of inequality: the place of young Goan men in a post-crisis UK labour market - McDowell, L; Rootham, E; Hardgrove, A (Wiley, 2015)
This article examines the ways in which young migrant men are constructed as potential employees in a British town where service sector employment, often on a casual or precarious basis, dominates the bottom end of the labour market. Low-wage jobs in many British towns are now constructed as feminized, low waged and demanding personal skills of empathy and servility. In this context, young men, and especially young men of colour, including recent in-migrants, are at a disadvantage, constructed by employers, agencies, co-workers and customers as less eligible workers than ‘locals’. We use the experiences of young men from Goa as a lens though which to trace the ways in which expectations and experiences when looking for employment produce a hierarchical division of labour in precarious jobs at the bottom end of the service sector.